Against the background of global climate changes, the current ecological situation of Azerbaijan’s water resources and the directions of efficient use - Khalilov, Ilgar; Eminov, Farhad (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
State of the problem. The article describes the full range of hydrological threats related to the limitation and pollution of the water resources of the Republic of Azerbaijan. It is noted that the consequences of year-by-year aggravation of hydrological threats are the increase of conflicts with neighboring states, the development of new centers of ecological instability, the republic’s socio-economic development programs are not fully implemented in the regions. It is known that the main features of Azerbaijan’s water resources are their limitation, uneven distribution, approximately 70% of surface water resources are formed outside the country’s borders and are seriously polluted when entering the country. The total water reserve of Azerbaijan is 35 billion cubic meters, of which 5 billion cubic meters is underground water. River water resources of the republic are 30.0 billion cubic meters, of which 10.0 billion cubic meters are local waters. Research object. Azerbaijan’s water resources, their modern ecological condition and directions for effective use. The purpose of the study. Based on the long-term observation data and climate forecasts of Azerbaijan, it is to show the scarcity of fresh water resources, the potential to be significantly affected by climate change, and the directions of efficient use. However, the ability to quantify future changes with hydrological changes and their impacts on systems and sectors is limited by uncertainty at all stages of the assessment process. Uncertainty arises from different socio-economic development scenarios, given different climate model forecasts, reduction of climate impacts to local and regional scales, impact assessment. In accordance with the UN Sustainable Development Goals, it is important to study its effects in the study area within the framework of climate action. Methodology. Generalization, statistical, systematic analysis and comparison methods were used in the preparation of the article. Scientific novelty of the research. Against the background of modern climate change, the ecological situation of Azerbaijan’s fresh water sources is analyzed and the characteristics of the use of water in various economic fields, the situation of pollution of transit river waters with industrial and domestic sewage of neighboring countries, and the harmful effects of their use on human health and environmental components are emphasized. Research results. In the article, the improvement of the national strategy in the implementation of the ecological-geographical assessment of water bodies in Azerbaijan, the implementation of projects supported by various international organizations, the application of river basin management plans to a larger number of rivers and the improvement of legislation for the purpose of protection, the implementation of international cooperation are among the necessary steps.